General optimal substation coverage algorithm for phasor measurement unit placement in practical systems - Pal, Anamitra; Mishra, Chetan; Vullikanti, Anil Kumar S; Ravi, S.S (IET generation, transmission & distribution, 2017)
The primary objective of the conventional optimal phasor measurement unit (PMU) placement problem is the minimisation of the number of PMU devices that, when placed in a power system, measure all bus voltages. However, due to advancements in the field of relay technology, digital relays can now act as PMUs. This has significantly reduced device costs. Moreover, although the goal is to observe all the buses, the devices themselves can only be placed in substations, whose upgrade costs are much higher than those of the devices. Considering these factors, the approach proposed here simultaneously optimises the number of substations where traditional PMUs and dual-use line relay PMUs can be placed. The general optimal substation coverage (GOSC) algorithm presented in this study is also able to incorporate practical requirements such as redundancy in the measurement of critical elements of the system, and estimation of the tap ratios of the transformers present. Simulation results indicate that the GOSC algorithm provides significant techno-economic benefits.